The effect of independence and gender of BOD, managerial and institutional ownership, and ownership concentration on tax aggressiveness - Butar-Butar, Dea Tiara Monalisa; Yunita, Lidia; Dewi, Sari (Journal of Contemporary Accounting, 2024)
This study examines the relationship between board independence, board gender, management ownership, ownership concentration and institutional ownership with tax aggressiveness in listed companies in Indonesia in the LQ45 reporting sector. Research data processing was executed with E-views 12 software. The source of research data is secondary data using library research methods, namely collecting information from various sources such as journals, theses, previous research, and others, as well as obtaining research sample data through the Indonesia Stock Exchange (IDX) website. The results showed that board independence had a significant positive effect on tax aggresiveness.